Regional-scale changes in diatom distribution in the Humboldt upwelling system as revealed by remote sensing: implications for fisheries - Jackson, T; Bouman, H; Sathyendranath, S; Devred, E (Oxford University Press, 2011)
A diatom-detection algorithm was parametrized for the Humboldt upwelling system using local cruise data that were first validated, then used to create monthly composites of diatom distribution from 0 to 40°S and 90 to 70°W for both normal and El Niño conditions. There was a 50% reduction in the areal extent of diatom-dominated waters during the peak of the 1997 El Niño. The extent of the coastward contraction in the diatom-dominated area varied along the South American coastline. These regional shifts in phytoand zooplankton communities would have increased food stress on local anchovy (Engraulis ringens) populations and could have contributed to diminished larval survival and landings the following year. A region of strong upwelling over the wide Peruvian continental shelf around 15°S was the only area that maintained a strong diatom population throughout the El Niño; the area may require special protection from fishing pressure in years following an El Niño event. © 2010 International Council for the Exploration of the Sea. Published by Oxford Journals. All rights reserved.